Analysis of Arabic Language Learning Methods to Improve Maharah Qiroah at Tsanawiyah Madrasah Level | Analisis Metode Pembelajaran Bahasa Arab untuk Meningkatkan Maharah Qiroah pada Tingkat Madrasah Tsanawiyah - M Ali Al Ridho; J. Sutarjo; Endang Munawar (An-nahdloh : Journal of Arabic Teaching, 2026)
Mastery of reading skills (maharah qirā’ah) at the Madrasah Tsanawiyah (MTs) level is often hindered by motivational barriers, difficulties in understanding language structures, and pedagogical boredom. This study aims to analyze the effectiveness of three learning methods SQ3R (Survey, Question, Read, Recite, Review), Qowaid wa Tarjamah (Grammar-Translation Method), and PQ4R (Preview, Question, Read, Reflect, Recite, Review) in improving students' reading competencies. This study employs a qualitative method with a library research approach, analyzing data from three relevant classroom action research studies. The results indicate three distinct but complementary patterns of success: (1) The SQ3R method proves effective in engineering reading interest and transforming passive students into active learners through systematic inquiry; (2) The Qowaid wa Tarjamah method shows strong relevance in strengthening students' grammatical foundations, achieving a mastery level of up to 100%; and (3) The PQ4R method effectively enhances deep understanding and memory retention through the reflection element, marked by a drastic increase in mastery from 20% to 95%. This study concludes that educators need to apply an eclectic approach by selecting adaptive methods according to the diagnosis of student problems, whether they are psychological, structural, or cognitive. Based on the analysis of the spike in learning outcomes that occurred in the three maharah qiroah methods, the most effective method in the context of drastic improvement is the PQ4R Method (Preview, Question, Read, Reflect, Recite, Review). Because, this method produces the most extreme increase in performance compared to other methods.